The role of airway hyperresponsiveness measured by methacholine challenge test in defining asthma severity in asthma–obesity syndrome. Issue 3 (June 2016) - Charron, Catherine B.; Pakhalé, Smita
Abstract : Purpose of review: Asthma is a complex disease defined by chronic inflammation of the airways. In research and clinical practice measures used for diagnosis, an assessment of control and severity of asthma are varied and there exists no gold standard. To date, several studies have explored the link between obesity and asthma although the exact mechanism is not yet fully understood. A study undertaken by our research group in 2015, on the effects of weight loss on asthma severity in obese asthmatics, demonstrated that an improvement in airway hyperresponsiveness could be achieved after significant weight reduction with a weight loss program. The objective of this article is to review the current literature for the primary and secondary outcomes studied to estimate the effects of weight loss on asthma severity in adults with obesity and asthma. Recent findings: A review of the most recent research conducted since 2014 demonstrates that effects of weight loss on asthma severity in adults with obesity and asthma has not been the focus of majority of the studies. Apart from our study published in 2015, very few studies used airway hyperresponsiveness as the primary or secondary outcome measure. The literature reveals that significant weight loss does, however, lead to improvement in asthma severity and control in adults with obesity and asthma. Summary: The current literature suggests that improvement in lung function requires moderate to significant (5–10%) weight loss in adults with obesity and asthma. However, with a few exceptions, the majority of these studies were small and used variable and questionable asthma severity outcome measures. There is an urgent need for standardization of diagnosis of asthma, study inclusion criteria, and outcome measures to assess asthma severity in research setting. Long-term effects of weight loss interventions on asthma severity and control, in adults with obesity and asthma, also remain unanswered.